Identification and quantification of potential wave energy in the coast of Atlántico state in Colombia (2017)
This paper describes the progress regarding the identification and quantification of potential wave energy in Atlántico state coast. The used methodology will serve as a starting point to establish the energetic potential in Colombia in this energy. The theoretical energetic potential estimated at the near shore in the Atlantic coast waves is approximately 1107 MW and this was possible with data that has been collected and processed since January 2016. We applied equations that take into account variables such as: significant wave height, period, sea water density, temperature and wind speed in the area. Also it is shown the progress of the near shore system design for the verification of the wave energetic potential consisting of a device which transforms kinetic energy of the sea waves into gravitational potential energy that is going to be used to move an alternating current generator.